Closed circular economy model of the forest sector in the regional aspect - Tereshina Maria; Yakovleva Elena; Titova Elena (BIO Web of Conferences)
The article presents a model of the circular economy in the context of the forest sector, emphasizing the importance of incorporating forest resources into circular supply chains that extend from the forest to consumers. Based on the logical structure of measuring the development of the circular economy in the forest sector and based on the availability of data, a system for assessing the indicators of the development of the circulareconomy in the forest sector was formulated, including financial, social, and environmental aspects, such as resource efficiency, environmental impact, economic efficiency and social well-being. Based on the results of the study, recommendations for the formation of a circular economy model in the forest sector were formulated.